Letter (translation) - Pla y Pla, Jaime
012a-0050-001 TRANSLATION. Department of the Interior. Intermunicipal Administrative Committee for Aragon. Control of (Child) Colonies, ronda universidad 33 BARCELONA. rec 9 Sept. To the President, Special Meeting Executive Committee LABOUR PARTY, BLACKPOOL. My Dear Sir, Impelled by the moral duty which my principles of humanitarianism inspire in me, and aware of the sentiments and the regard which the LABOUR PARTY entertains towards the democratic and Republican cause for which Spain is fighting, I taking the liberty of approaching you and all the representatives present at the Special Meeting of the Executive Committee of the LABOUR PARTY, bringing to your knowledge the existence of more than TEN THOUSAND FIVE HUNDRED BOYS AND GIRLS, evacuated from Aragon, as the result of the retreat of the Republican troops from this region, and which children we must provide with a healthy and clean home to replace what they have lost. This Inter-municipal Administrative Committee for Aragon, set up by a Decree of the Republic on 3rd June last, with the object of attending to thousands of evacuated Aragonese, especially the children, appeals to the humanitarian sentiments of the whole world, for co-operation in the maintenance end relief of the children of Aragon. For this purpose we are proposing to set up TWO HUNDRED COLONIES, each with fifty boys or girls, in areas far from the theatre of war, including some in foreign countries, so that the children of Aragon may be properly looked after. For our TEN THOUSAND FIVE HUNDRED EVACUATED CHILDREN (10,614 according to official figures up to date) we urgently require: APPAREL, bed-linen, clothing, boots, &c. &c., FURNITURE, 11,000 beds, mattresses, sheets, blankets, &c. &c., TABLES, chairs, plates, &c. &c. FOODSTUFFS, vegetables, conserves, &c. &c., EMERGENCY MEDICINE CHESTS and adequate supply of medicaments for children, School MATERIAL, craft rooms and offices, farms, clothing workrooms, TRANSPORT, lorries, 'buses, ambulances, &c. &c. Consequently, and having in mind the TEN THOUSAND FIVE HUNDRED children, and being disposed at all costs and by every possible method to fill their needs, and particularly to give them a lodging, I take the liberty of approaching you to ask you in their name for your assistance and personal and representative collaboration, as well as that of the LABOUR PARTY, of which you are the distinguished Chairman. Yours fraternally end respectfully, (signed) Jaime Plá y Plá. 292/946/12a/50